The influence of compaction technology on the internal structure of the asphalt mixture - Iwański, Marek; Durlej, Małgorzata (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
A fundamental property of asphalt mixtures is the void content. It significantly influences their resistance to water and frost. Currently, this is traditionally determined using the hydrostatic method. This method may not be effective for environmentally friendly mixtures produced using Warm Mix Asphalt technology. They are produced and compacted at a lower temperature than traditional methods. Therefore, they may be characterized by abnormal void content in the internal structure. Microtomographic analysis can now be used to thoroughly examine the internal structure of asphalt mixtures in terms of pore size distribution, interconnection patterns, and their arrangement. This is particularly important in identifying changes occurring within the asphalt mixture as a result of the destructive effects of water and frost. Studies were conducted on the effect of vibratory and Marshall impact compaction on the internal structure of the asphalt mixture. Mixture samples were analyzed before and after conditioning according to AASHTO T283 and WT-2 2014 standards. It was found that the compaction method affects the distribution and interconnection of pores. Samples compacted using the vibratory method are more uniform in terms of the distribution of large and interconnected pores within the asphalt mixture structure. Smaller pores with a volume of 0 to 0.5 mm3 occur between the mini-pores, increasing the resistance of the asphalt mixture to water and frost. It was found that, in addition to extremely small pores, interconnected pores have the greatest impact on the mixture resistance to water and frost.